Immune checkpoint inhibitors in the treatment of hepatocellular carcinoma - Akbulut, Zeynep; Aru, Başak; Aydın, Furkan; Yanıkkaya Demirel, Gülderen (Frontiers in Immunology, 2024)
Despite advances in cancer treatment, hepatocellular carcinoma (HCC), the most common form of liver cancer, remains a major public health problem worldwide. The immune microenvironment plays a critical role in regulating tumor progression and resistance to therapy, and in HCC, the tumor microenvironment (TME) is characterized by an abundance of immunosuppressive cells and signals that facilitate immune evasion and metastasis. Recently, anti-cancer immunotherapies, therapeutic interventions designed to modulate the immune system to recognize and eliminate cancer, have become an important cornerstone of cancer therapy. Immunotherapy has demonstrated the ability to improve survival and provide durable cancer control in certain groups of HCC patients, while reducing adverse side effects. These findings represent a significant step toward improving cancer treatment outcomes. As demonstrated in clinical trials, the administration of immune checkpoint inhibitors (ICIs), particularly in combination with anti-angiogenic agents and tyrosine kinase inhibitors, has prolonged survival in a subset of patients with HCC, providing an alternative for patients who progress on firstline therapy. In this review, we aimed to provide an overview of HCC and the role of the immune system in its development, and to summarize the findings of clinical trials involving ICIs, either as monotherapies or in combination with other agents in the treatment of the disease. Challenges and considerations regarding the administration of ICIs in the treatment of HCC are also outlined.